Religiosity, depression and cognitive impairment among hemodialysis patients in Hospital Kuala Lumpur / Dr. Nor Jannah Nasution Raduan - Raduan, Dr. Nor Jannah Nasution (2016)
Background: Depression and Cognitive impairment are two most common complications of patients on hemodialysis. Religiosity has been found to have a positive effect and minimized these problems. Objective: To study religiosity and its relationship with depression and cognitive impairment among hemodialysis patients in Hospital Kuala Lumpur. Methodology: This is a cross-sectional study involving 110 hemodialysis patients in Hospital Kuala Lumpur. The samples were recruited through universal sampling. The assessments were done during the dialysis treatment and within two hours of the hemodialysis. The patients were assessed with Beck Depression Inventory- Malay (BDI), Malay Mini International Neuropsychiatric Interview - Malay (MINI), Malay Montreal Cognitive Assessment (MOCA) and Duke University Religious Index Malay (DUREL-M). Descriptive analysis was performed, followed by multiple logistic regression analysis. Results: This study found that 18.2% patients had depression and 48.2% had cognitive impairment. The factors significantly associated with depression were patients having no current episode of depression in M.I.N.I Depression (OR= 0.047; 95% CI= 0.012-0.176), unmarried status (OR= 3.906; 95% CI= 1.409-10.830), high intrinsic religiosity (OR= 0.329, 95% CI= 0.116-0.935) and low education level (OR= 3.056; 95% CI= 1.108, 8.427). Factors found to be significantly associated with cognitive impairment were low education level (OR=7.714; 95% CI= 2.954-20.147) and unemployment (OR= 3.299, 95% CI=1.443-7.541). Conclusion: Depression and cognitive impairment are prevalent in hemodialysis patients; they are significantly associated with high intrinsic religiosity, unmarried status, unemployment and low education level. Routine screening, multidisciplinary management and enhancing religiosity of hemodialysis patients are important preventive measures.